THE DESIGN OF THE PARKING LOT LAYOUT OF HKBP MULTI-PURPOSE BUILDING IN TANGERANG CITY - Muhammad Zulyadaen; Edison Hatoguan Manurung (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2025)
HKBP Church has an important parking lot to facilitate the parking needs of the congregants who want to worship at the church. The parking lot is located around the HKBP Tangerang City Multipurpose Building, which is still functional, but the parking capacity could not accommodate the number of vehicles needed. Aims: The objective of this article is to review the parking layout design of the HKBP Tangerang City Multipurpose Building in order to optimize the number of parking vehicles. Methodology and results: The 90° parking pattern for 40-motorcycles and the lack of sufficient parking spaces clearly interfere the available area for other facilities, making parking a very important issue. Conclusion, significance and impact study:The study employed the observation method, which was carried out by several field surveyors. The results were considered as 'primary data', while secondary data were obtained from various references and previous studies. This paper demonstrates that effective parking lot management requires an optimal parking pattern and flow. Through simulation, it was determined that a 45° angle parking pattern can accommodate 200 motorcycles, while a 90° angle pattern can accommodate 100 cars.